Ultrasound versus MRI in common fibular neuropathy. Issue 6 (21st March 2017) - Bignotti, Bianca; Assini, Andrea; Signori, Alessio; Martinoli, Carlo; Tagliafico, Alberto
ABSTRACT: Introduction: We prospectively compared ultrasound (US) and MRI in patients with common fibular neuropathy. Methods: Forty adult patients with clinical suspicion of common fibular neuropathy and 40 healthy controls underwent both US and MRI. US and MRI datasets were randomized for prospective reading. Results: The overall sensitivity of US and MRI for diagnosing fibular neuropathy was 90% (95% confidence interval [CI], 79.7%‐97.3%) and 87.5% (95% CI, 71.55%‐93.1%), respectively. The overall specificity of US and MRI was 92% (95% CI, 77.45%‐96.1%) and 85% (95% CI, 73.3%‐94.4%), respectively. The overall sensitivity and specificity of US combined with MRI were 94% (95% CI, 0.80%‐0.99%) and 84% (95% CI, 0.70%‐0.91%), respectively. Overall intra‐ and inter‐observer agreements among 3 readers were 0.76% (95% CI, 0.62%‐0.85%) and 0.74% (95% CI, 0.65%‐0.81%). Conclusions: US diagnostic accuracy for common fibular neuropathy was slightly higher than that of MRI. Muscle Nerve 55 : 849–857, 2017